(untitled) (Economic and Political Thought, 2015)
From 1 July to 31 December 2014, Italy held the Presidency of the Council of the European Union for the seventh time in the history of the European Communities. The Presidency took place in a very difficult period in the history of integration: the economic and financial crisis of the Eurozone was not overcome, there were tensions in the relations with Russia in connection with the situation in the east of Ukraine, there was a threat resulting from the unstable situation in the Mediterranean and there were changes in the most important posts of the European institutions after the elections to the European Parliament. The main priorities of the Italian Presidency, also adopted by the presidency trio with Latvia and Luxemburg, focused on the pro-growth policy in economy, completion of the development of the banking union in the financial area and active foreign policy, the main elements of which was solidarity in the Mediterranean policy (combating illegal immigration), emphasising strategic relations with Russia, reviving economic relations with the countries of Asia and the Pacific and economic relations with the United States. Due to Italy’s internal weakness reflected in unstable political situation and economic crisis, the Presidency managed to implement only some of the plans. It was the Presidency that mostly passed unnoticed.